IMMUNOLOGICAL IMPLICATIONS OF SYSTEMIC RISK FACTORS FOR PERIODONTAL DISEASE - Petra Surlin; Liliana Foia; Sorina Solomon; Popescu Dora; Alexandra Martu; Simona Popa; Mihail Virgil Boldeanu; Valentin Barbu; Ion Rogoveanu (Romanian Society of Oral Rehabilitation, 2019)
The periodontal apparatus is very well connected with the rest of the human body, by means of vascular, lymphatic and nervous structures. These connections make the periodontal structures easily accessible to different distant pathologic mechanisms, such as inflammatory reactions, that can influence the onset and evolution of periodontal diseases. In certain situations, these influences have a mutual nature, transforming the relationship of the periodontal pathology with the systemic conditions into a bi-directional one. Understanding the mechanisms that drive and promote these pathogenic connections is important for offering periodontal patients a comprehensive treatment and for including periodontal screening for certain systemic diseases' patients.